Analysis of Work Environment and Motivation on Employee Performance - Aji, Muhammad Untung Seno; Zaharuddin; Adiputra, I Gede (Journal of Trends Economics and Accounting Research, 2025)
This study examines the influence of Work Environment and Motivation on Employee Performance at PT Rupa Aestetika Teknologi Aktual. Employing a quantitative approach with a survey research design, this study implements a saturated sampling technique by involving the entire population consisting of 83 employees as respondents. Primary data collection was conducted through structured questionnaire instruments. Data analysis using multiple linear regression reveals that Work Environment has a positive and significant influence on Employee Performance, while the Motivation variable also demonstrates a positive and significant impact on Employee Performance. Based on these analytical findings, this study recommends optimizing the work environment through enhanced facilities and conducive working conditions, as well as adjusting compensation systems and fulfilling employees' physiological needs as fundamental efforts to improve performance. The theoretical implications of this research contribute to the development of human resource management literature, particularly in the context of the relationship between work environment, motivation, and employee performance.